2015
DOI: 10.1073/pnas.1508831112
|View full text |Cite
|
Sign up to set email alerts
|

Development and aging of cortical thickness correspond to genetic organization patterns

Abstract: There is a growing realization that early life influences have lasting impact on brain function and structure. Recent research has demonstrated that genetic relationships in adults can be used to parcellate the cortex into regions of maximal shared genetic influence, and a major hypothesis is that genetically programmed neurodevelopmental events cause a lasting impact on the organization of the cerebral cortex observable decades later. Here we tested how developmental and lifespan changes in cortical thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
225
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 274 publications
(273 citation statements)
references
References 108 publications
35
225
2
Order By: Relevance
“…This finding fits with the notion that GCA is supported by distributed brain networks (44,45). Using genetically defined cortical clusters (6,35), there was evidence that especially prefrontal and medial and posterolateral temporal clusters related more strongly to GCA. Most previous studies have focused on cortical volume or thickness, but the present results correspond with previously reported findings on areacognition relationships (24) in a sample not overlapping with the current developmental cohort wherein the region was currently identified.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This finding fits with the notion that GCA is supported by distributed brain networks (44,45). Using genetically defined cortical clusters (6,35), there was evidence that especially prefrontal and medial and posterolateral temporal clusters related more strongly to GCA. Most previous studies have focused on cortical volume or thickness, but the present results correspond with previously reported findings on areacognition relationships (24) in a sample not overlapping with the current developmental cohort wherein the region was currently identified.…”
Section: Discussionsupporting
confidence: 86%
“…Previous research has shown that the cortex can be divided into regions of maximum shared genetic variance, and these regions can further be organized into superordinate clusters based on genetic similarity. As described above, we have recently shown that developmental and adult age-related changes in cortical thickness follow this genetic organization of the cerebral cortex (6). The most fundamental genetic influence on cortical surface area goes along an anterior-posterior axis (35).…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations